EMPLOYEE PERFORMANCE ANALYSIS OF PERMATA PAMULANG HOSPITAL ADMISSION UNIT IN 2022 - Andriyani; Muhammad Labib; Listya Nur 'Aini; Hardiman SG (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Human resources play an important role in a company because they are a key factor in managing the company's goals. Performance assessment is one of the assessments of an employee's ability to exercise his authority. Things that can affect good employee performance include motivation, employee work discipline, supervision, leadership style, and more. The objective of this study is to see how the role of Human Resources (HR) in developing the performance of employees in the Registration Unit of the Jewelry Pamulang Hospital. The study uses a qualitative approach with descriptive methods. This research was conducted to understand more deeply and explain the experiences experienced by individuals through in-depth interviews. The data processing of this research uses triangulation of sources and methods. The informants in this study are five people who are key informants, primary informants, and supportive informants. The study was conducted at the Pamulang Jewelry Hospital from October 2022 to January 2023. The results of this study indicate that the performance of employees in the Registration Unit is good, for employees, it is almost disciplined but still, there are employees who are less disciplined. Employees' work also requires motivation from their superiors so that their performance is better. Motivation is essential because employees' motivation can work better and enthusiasm in their performance. Besides, the employee's work discipline at the Yellow Pamulang Hospital Registration Unit is quite good, because employees already understand each other's responsibilities.